Ethnobotanical survey of medicinal plants traditionally used for eczema treatment in Morocco - Metni, Khairo El Baria; Boutaj, Hanane; Mesbahi, Qamar; Oufkir, Noureddine; Ameggouz, Mouna; El Bassami, Siham; Qostal, Mariem; Cherkani Hassani, Abha; Benzeid, Hanane (Ethnobotany Research and Applications, 2025)
Background: This study aimed to document and analyze the traditional use of medicinal plants for treating eczema in Morocco, with the goal of preserving local knowledge and identifying potential candidate species for further pharmacological investigation. By focusing on the practices of local herbalists, we sought to establish a comprehensive database of plants commonly employed for dermatological care, particularly eczema. Methods: Semi-structured questionnaires were administered to 200 herbal practitioners across various Moroccan regions (Marrakech, Casablanca, Rabat, Fez, Oujda) in their native language, Darija. The plant species mentioned were cross-referenced with relevant literature, and the collected data were systematically analyzed. Results: The ethnobotanical survey documented 107 plant taxa belonging to 48 botanical families, with Asteraceae being the most frequently cited. Leaves were the most commonly used plant part, and powdering was the primary preparation method. Remedies were predominantly administered as poultices, typically applied at night. Notably, twenty-three of the documented species have been previously reported in the scientific literature for their efficacy in managing dermatological conditions, including eczema. Conclusions: This study highlights the importance of ethnobotanical surveys in preserving traditional knowledge and identifying medicinal plants in Morocco for eczema treatment. However, further laboratory studies are needed to validate their therapeutic potential. Keywords: Ethnobotanical survey, traditional uses, treatment, eczema, medicinal plants, Morocco.